2017
DOI: 10.1108/apjba-10-2016-0095
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of public-private partnership (PPP) voluntary information

Abstract: Purpose The purpose of this paper is twofold: first, it seeks the perception of public-private partnership (PPP) experts on the importance of desirable PPP information that can be voluntarily reported by the private sector; and second, it determines the extent and quality of voluntary disclosure of PPP information by private entities. Design/methodology/approach In achieving the first objective, the study uses a questionnaire survey. The questionnaire was distributed to PPP experts and 25 usable responses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…As such, a respondent driven sampling method, which is an advanced snow balling method that eliminates bias in a hidden population, was adopted to determine the sample size of the study (Salganik and Heckathom, 2004). The PSOs constitute a hidden population because they have policies for inadequate disclosure of PPP projects' information, which create difficulty in accessing such information (Musawa et al, 2017). The sample size was determined by building up a referral chain in the survey through a selection of at least one respondent from the professionals from the PSOs.…”
Section: Methodsmentioning
confidence: 99%
“…As such, a respondent driven sampling method, which is an advanced snow balling method that eliminates bias in a hidden population, was adopted to determine the sample size of the study (Salganik and Heckathom, 2004). The PSOs constitute a hidden population because they have policies for inadequate disclosure of PPP projects' information, which create difficulty in accessing such information (Musawa et al, 2017). The sample size was determined by building up a referral chain in the survey through a selection of at least one respondent from the professionals from the PSOs.…”
Section: Methodsmentioning
confidence: 99%
“…The PPP is increasingly becoming the preferred form of delivering public services in developing countries [12,13]. In several countries, pressure from the lowering of public debt has prompted their policymakers to include private sector companies in several investments of economic and social infrastructure, such as toll roads, colleges, hospitals, car parks and facilities [14].…”
Section: Introductionmentioning
confidence: 99%
“…13, x FOR PEER REVIEW 9 of 14 each other. According to their opinion, the concept of PPP is new in Pakistan in comparison with China and India; secondly, there is a significant difference in the economies of Pakistan, China and India.…”
mentioning
confidence: 99%
“…Similarly, Hodge (2006) who reviewed Australia’s PPP policies including the parliamentary inquiries on PPP projects concluded that PPP arrangement in reality, “is a two-way government business deals” which typically isolate other affected stakeholders as a result of not disclosing information. In a recent study by Musawa et al (2017) on the extent of voluntary disclosure of PPP information by private companies in Malaysia also revealed that very little information being disclosed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Public private partnership (PPP) refers to the collaboration between public sector and private sector companies in designing, building, financing and/or operating public infrastructure for the benefit of the society (Musawa et al , 2017). It is a well-known procurement approach for providing public infrastructure and services which has been adopted in various developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%